Nutritional status and knowledge about nutrition during pregnancy among pregnant and postpartum women (Northern International Medical College Journal, 2015)
Objective : To assess the nutritional status and the level of knowledge about nutrition during pregnancy among pregnant and postpartum women attended community clinics in selected villages.Methods : This descriptive, cross-sectional study was done in three selected villages of Sirajganj, Kishoreganj and Tangail districts during July 2014. Fifty six pregnant and 46 postpartum women were selected from community clinics by purposive sampling technique. Data were collected through face to face interview by a pretested questionnaire. Height and weight were measured to calculate BMI health workers of community clinic.Results : The results of the study revealed significant number (23.5%) of pregnant women were found to be underweight by calculating the BMI. However, knowledge about the consequences of malnutrition in pregnancy, and the amount and types of food to be taken during pregnancy was found unsatisfactory. The level of education and occupation were not significantly associated with nutritional status of the respondents.Conclusion : The study revealed that high percentage of rural mothers was malnourished and the knowledge about nutrition during pregnancy was found unsatisfactory. Therefore, implementation of nutritional programs with specific emphasis on nutritional education in pregnancy during the antenatal visits is considered essential for rural women.Northern International Medical College Journal Vol.6(2) 2015: 61-63